Pengaruh Motif Selfie Terhadap Keterbukaan Diri Generasi Milenial - Merlin Merlin; Dinda Rakhma Fitriani (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
Smartphones are mobile phones that can function like a computer with various advanced features to support the activities of users. One of them is the camera to create quality photos that outperform photographic tools. The development of smartphone front camera technology encourages the emergence of selfie phenomena among millennials. The millennial generation is the generation that is heavily influenced by smartphones, the internet, and social media. One of social media that focuses on visual content with text as a complement is Instagram. This study aims to determine the effect of Instagram selfie on Millennial Generation self openness. The theory used in this research is The Uses and Gratification Theory. The method used in this study is a quantitative method with a positivist paradigm and researchers collect the data using questionnaire. This research was conducted in millennials with an age range of 19-39 years. The sample in this study amounted to 100 respondents, using the Cluster Sampling technique. From the correlation analysis between Selfie Motive variables on Instagram and Self Disclosure variables have a fairly strong and positive relationship. After the regression test, the equation Y = 12,009 + 1,027 X was produced with the result of a coefficient of determination of 52.1%, which indicates that the self-disclosure of the millennial generation is influenced by selfie motives on Instagram, while the rest is caused by other factors.